Ocorrência do gênero Stiropius Cameron, 1911 (Hymenoptera, Braconidae, Rogadinae) em Mata Atlântica ombrófila densa da região sudeste do Brasil - Brunelli, Carlos Augusto Prates (Universidade Federal de São Carlos, 2008)
The collection and maintenance of the material used in this paper were financed by the Biota/ FAPESP project (process 1998/05083-0). The main objective of this study is to come to know the Stiropius Cameron, 1911 (Hymenoptera: Braconidae: Rogadinae) fauna in 8 localities in the Atlantic Rain Forest distributed by the Southeastern part of Brazil, aiming to amplify the taxonomic knowledge of the group mentioned before. The genus includes 18 described species, only one from Brazil. Using Malaise and Moericke traps and sweeping of the vegetation 44 units of the genus Stiropius were collected and identified as 31 different species: 5 were already described by ACHTERBERG (1995) in Central America and 26 new species: 7 in Sao Paulo State, 12 in Rio de Janeiro State and 7 in Espirito Santo State. The richness of species is significant when compared to the number of samples that were found, suggesting that the genus Stiropius constitutes a diverse group in the Atlantic Rain Forest and indicates the shortage and viability of new studies with the genus Stiropius, approaching the Rain Forest biome and the south-American continent in general, since reviews of the genus before this paper were carried only for North and Central America.
Keywords: Hymenoptero; Taxonomia; Braconidae; Mata Atlântica; Parasitóides; CIENCIAS BIOLOGICAS::ECOLOGIA